The potential impact of climate change on Nigerian agriculture - Ajetomobi, Joshua; Ajakaiye, Olusanya; Gbadegesin, Adeniyi (International Food Policy Research Institute, 2015)
This report examines how extreme weather conditions have affected the mean and variance of the yield of 18 food crops in Nigeria over a period of 42 years (1971-2012). The analysis at the State level was reduced to five Agricultural Transformation Agenda (ATA) priority crops and covered 22 years (1991-2012) due to data scarcity. The framework for the analysis consists of a stochastic production function suggested by Just and Pope (1978, 1979). The results show that the productivity of more than half of the staple crops in Nigeria is threatened by increase in total annual rainfall and extreme temperature nationally and across states in Nigeria. However, such increase is found to have beneficial effects on the productivity of a few crops grown in Northern Nigeria. The economic impact shows that extreme temperature will cause a considerable annual loss in value for most crops except few that are are grown mainly in Northern Nigeria (Borno, Yobe, Kaduna, Kano and Sokoto states) such as millet, melon, and sugarcane.